2019
DOI: 10.13066/kspm.2019.14.1.121
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cervical Stabilization Exercise Using Pressure Biofeedback on Neck Pain, Forward Head Posture and Acoustic Characteristics of Chronic Neck Pain Patients with Forward Head Posture

Abstract: PURPOSE: This study was conducted to measure the effects of cervical stabilization exercises on neck pain, forward head posture, and the acoustic characteristics frequency and amplitude modulation of patients with chronic neck pain caused by forward head posture using pressure biofeedback. METHODS: 20 patients with chronic neck pain and voice disorders presenting at the S Exercise Center in Daegu, Korea, were included in the study. A cervical stabilization exercise program of 50 minutes per session was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Stabilization is the ability of a person to consciously or unconsciously control large or fine movements of a joint [16]. Stabilization exercise had significant effects on pain and psychological improvement in individuals with chronic neck pain [17,18]. Stabilization is not only required for the neck, but it is also required for the nerve roots of the body, strength and endurance, and flexibility [19].…”
Section: Introductionmentioning
confidence: 99%
“…Stabilization is the ability of a person to consciously or unconsciously control large or fine movements of a joint [16]. Stabilization exercise had significant effects on pain and psychological improvement in individuals with chronic neck pain [17,18]. Stabilization is not only required for the neck, but it is also required for the nerve roots of the body, strength and endurance, and flexibility [19].…”
Section: Introductionmentioning
confidence: 99%
“…The chin tuck exercise in CSRE is thought to leaf to increased cervical ROM and decreased pain by reducing the strain on the sternocleidomastoid muscle due to forward head posture and improving neck alignment by activating the longus coli (deep neck flexor). [ 10 , 55 ] Patients with scapulothoracic dysfunction and NP show weakening of the serratus anterior, [ 56 ] and the standing chest press exercise in our study activated the serratus anterior, thereby reducing scapulothoracic dysfunction and NP. A high level of activity in the upper trapezius increases scapulothoracic dysfunction and NP.…”
Section: Discussionmentioning
confidence: 62%
“…FHP is a poor habitual neck posture that is defined by the forward translation of the cervical vertebrae and hyperextension of the upper cervical vertebrae [2]. Continuous FHP adds the load to posterior cervical structures for instance, ligament and transforms scapular kinetics and kinematics [3], affects the quality of life and activities of daily living [30] Previous research demonstrated that cervical stabilization exercises have a positive effect on FHP [4][5][6][7]. Thoracic stretching exercises can improve postural alignment related to FHP.…”
Section: Introductionmentioning
confidence: 99%